2021
DOI: 10.1186/s43045-021-00155-z
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 infection have an impact on children’s psychological problems?

Abstract: Background Coronavirus disease 2019 (COVID-19) has a significant impact on children, adolescents, and their families. So, the purpose of this study is to investigate the prevalence of children’s psychological problems during the COVID-19 pandemic and their association of COVID-19 infection in children and their risk factors. A cross-sectional study was conducted on 148 children aged 6–12 years old categorized into 2 groups based on COVID-19 infection history. Participants were assessed by the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…Moreover, there is direct evidence that COVID-19 affected psychiatry problems and brain function. Previous studies indicated that children infected with COVID-19 were more likely to have psychological issues, such as affective disorders, somatic, internalizing, and externalizing problems by comparing the outcome in the children and pre-schoolers who had COVID-19 and those who did not ( 33 , 34 ). The hypothalamic-pituitary-adrenal axis, which can interfere with different physiological processes throughout the early stages of development, was affected by the COVID-19 pandemic distress by increasing the creation and release of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is direct evidence that COVID-19 affected psychiatry problems and brain function. Previous studies indicated that children infected with COVID-19 were more likely to have psychological issues, such as affective disorders, somatic, internalizing, and externalizing problems by comparing the outcome in the children and pre-schoolers who had COVID-19 and those who did not ( 33 , 34 ). The hypothalamic-pituitary-adrenal axis, which can interfere with different physiological processes throughout the early stages of development, was affected by the COVID-19 pandemic distress by increasing the creation and release of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Be infected with COVID-19 were more likely to have psychological issues ( 33 , 34 ). To explore the infection condition, we have surveyed whether these students and their relatives had a COVID-19 infection or not in February 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that during virus provoked pandemics or epidemics larger percentage of respondents reported anxiety or worries. [14][15][16] Coronavirus disease is ever-evolving since it started in 2019 till date. The data on treatment, vaccines, or scientific data on any long-term impact on health are insufficient till now for the adolescent population.…”
Section: Discussionmentioning
confidence: 99%
“…Academic performance may be impacted by poor sleep quality, somatization, depression, anxiety, post-traumatic stress disorder, and psychosis after infection [ 2 , 3 ]. Similarly, withdrawal, anxiety/depression, physical difficulties, internalizing problems, and externalizing problems may have impacted the academic performance of younger age groups [ 4 ]. Infection or death of family members as a result of Covid-19; social and parental issues; increased family expenses; and a decrease in family income indirectly affect academic achievement [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, withdrawal, anxiety/depression, physical difficulties, internalizing problems, and externalizing problems may have impacted the academic performance of younger age groups [ 4 ]. Infection or death of family members as a result of Covid-19; social and parental issues; increased family expenses; and a decrease in family income indirectly affect academic achievement [ 4 ]. During the Covid 19 outbreak, there were also considerable levels of fear and stigmatization [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%